KESIAPAN SEKOLAH DASAR TERHADAP TUNTUTAN ABAD KE-21 MELALUI CRITICAL DAN COMPUTATIONAL THINKING - Lailati Rohmah; Sucilia Tri Lestari; Bianca Ayu Prastika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the readiness of elementary schools in developing critical thinking and computational thinking skills as learning demands of the 21st century. The research uses a qualitative approach with a case study design carried out at SD Al Firdaus Surakarta. Data were collected through in-depth interviews, participatory observations, and documentation studies of teachers and students of grade V. Data analysis was carried out using the Miles and Huberman model which included data reduction, data presentation, and conclusion drawn. The results of the study show that teachers have a good initial understanding of the essence of 21st century learning, even though the application of critical thinking and computational thinking is still implicit. The Unit of Inquiry (UOI)-based school curriculum allows for cross-subject integration through research-based projects and digital technologies. Students show positive initial readiness in critical and computational thinking, while schools have provided digital facilities. Nevertheless, optimizing the use of technology and strengthening teachers' pedagogic literacy is still needed so that 21st century learning can be carried out in a sustainable and measurable manner